EFEKTIVITAS PENERAPAN RESTITUSI BAGI KORBAN TINDAK PIDANA PERDAGANGAN ORANG YANG BERKEADILAN PANCASILA - Kriswiansyah, Zarra Devina (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This study aims to examine how the effectiveness of restitution for Victims of Human Trafficking based on Pancasila values of justice. The type of research used by the writer for this study is normative-empirical legal research, and the nature of the research uses an applied perspective. Primary, secondary, and tertiary legal material is used for sources of this study. To collect the data and legal material the writer do studying literature and conducting interviews. The result of this study shows that the application of restitution that has been implemented in the Human Trafficking case viewed from the perspective of its effectiveness is still not effective in fulfilling the Pancasila value of justice because not all losses suffered by victims can be recovered. This is caused by several factors such as legal factors, law enforcement factors, and legal facilities. In an attempt to optimize the effectiveness of the implementation of restitution based on Pancasila values of justice, which in principle must consider the fairness between the Accused and the Victim, namely based on the principles of An Effective Remedy, the Principle of Victim Reparation, and the Principle of legal protection within the judicial and/or administrative system.